2021
DOI: 10.1155/2021/5433742
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Endothelin-1 and Calcitonin Gene-Related Peptide Concentrations in Patients with Cervical Radiculopathy after Wrist-Ankle Acupuncture-Moxibustion and Hot Compression with Chinese Herbal Medicine

Abstract: Objective. This study aimed at investigating the effects of wrist-ankle acupuncture-moxibustion and hot compression with Chinese herbal medicine on pain symptoms, endothelin-1 (ET-1), and calcitonin gene-related peptide (CGRP) concentrations of patients with cervical radiculopathy (CR). Methods. A total of 82 patients with CR were randomly divided into the study group and control group, with 41 cases in each group. The control group was treated with standard treatment. In addition to standard treatment, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Only one study reported the adverse reactions, which occurred in Fu's Subcutaneous Needling group of 3 patients with local bleeding after the treatment. Regarding the primary outcome measures, 27 studies reported the VAS scores [ 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], 9 studies reported the NDI scores [ 18 , 21 , 23 , 26 , 32 , 34 , 35 , 40 , 44 ], and 6 studies reported the TY scores [ 21 , 27 , 33 , 36 , 41 , 43 ]. As for the diagnostic criteria, 18 studies adopted the “Standard for diagnosis and efficacy evaluation of Chinese Medicine syndromes and diseases” [ 17 ], 7 studies adopted the “Summary of the Second Symposium on Cervical Spondylosis” [ 45 ], 1 adopted “The experts consensus on the classification, diagnosis and non-surgical treatment of cervical spondylosis(2018)” [ 46 ], we found the diagnostic criteria involved have high similarity between each other after reading and comparison.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one study reported the adverse reactions, which occurred in Fu's Subcutaneous Needling group of 3 patients with local bleeding after the treatment. Regarding the primary outcome measures, 27 studies reported the VAS scores [ 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], 9 studies reported the NDI scores [ 18 , 21 , 23 , 26 , 32 , 34 , 35 , 40 , 44 ], and 6 studies reported the TY scores [ 21 , 27 , 33 , 36 , 41 , 43 ]. As for the diagnostic criteria, 18 studies adopted the “Standard for diagnosis and efficacy evaluation of Chinese Medicine syndromes and diseases” [ 17 ], 7 studies adopted the “Summary of the Second Symposium on Cervical Spondylosis” [ 45 ], 1 adopted “The experts consensus on the classification, diagnosis and non-surgical treatment of cervical spondylosis(2018)” [ 46 ], we found the diagnostic criteria involved have high similarity between each other after reading and comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 28 studies involved, 27 studies [ 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ] evaluated the VAS scores as an outcome measure. the meta-analysis forest plot shows that the curative effect of Acupoint catgut-embedding was better than Conventional acupuncture (SMD = 2.68, 95 % CI [−3.27, −1.69], Z = 5.28, P < 0.00001, I 2 = 89 %, 3RCTs), Needle Knife superior to Conventional acupuncture (SMD = 2.83, 95 % CI [−4.14, −1.52], Z = 4.24, P < 0.0001, I 2 = 95 %, 5RCTs), while Warm needle was better than Conventional acupuncture (SMD = 1.32, 95 % CI [−1.79, −0.84], Z = 5.46, P < 0.00001, I 2 = 64 %, 3RCTs).…”
Section: Directly Compared Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations